PENERAPAN METODE STORYTELLING DALAM SEJARAH KEBUDAYAAN ISLAM UNTUK ANTUSIASME DAN DAYA INGAT SISWA DI MI - Tsania Putri, Idzni; Sulistiawati, Dita; Khusna, Siril; Sabrina, Alda Falihatus; Mardianingsih, Tri; Hidayah, Difa Puji; Khannaturrofiqoh; Rif'iyati, Dian (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the application of the storytelling method in Islamic Cultural History learning to increase student enthusiasm and retention at an Islamic Elementary School (MI) in Pekalongan Regency. The background to this research stems from low student interest in Islamic Cultural History lessons, which are often delivered monotonously, resulting in students being less active and having difficulty remembering the material. The storytelling method is considered capable of creating an interactive and meaningful learning atmosphere through the power of stories in conveying historical and religious values. This study used a qualitative literature approach with a literature review method. The research subjects were MI students, and data were collected through several journal references and articles. Data analysis was conducted thematically with a focus on increasing student enthusiasm and retention. The results showed that the application of storytelling had a positive impact on student learning motivation. Stories about Islamic figures, told expressively, captured students' attention and built emotional engagement, thus facilitating their recall of historical events. In conclusion, the storytelling method has proven effective in improving the quality of Islamic History learning, particularly in terms of student engagement and memory retention.